Modal Sosial Kelompok Tani Hutan Santuso II dalam Pengembangan Kapulaga di Desa Sumberpakem Kecamatan Sumberjambe Kabupaten Jember - Nadira Tri Hapsari; Rokhani Rokhani (Fakultas Pertanian Universitas Jember, 2020)
This purpose of this researchis to analyza social capital based on networks, norms and trust as in the Santuso II Forest Farmers Group in cardamom development. This research uses a qualitative descriptive method. Data collection methods used are observation, interview and documentation. The key informants were the head of the group, and the supporting informants were members of farmer groups, forestry extension agents, Sumberpakem Village secretaries and Chair of the International Association of Students in Agriculture and Related Sciences at the University of Jember. Data analysis used the Miles and Huberman method with 4 stages, namely data collection, data reduction, data presentation and conclusion drawing. The results showed that networking occurs between personal, personal networks with institutions and institutional networks with institutions. The elements of norms consist of written norms and unwritten norms and beliefs that appear in the Santuso II Forest Farmer Group based on the relationship between members of the farmer group and institutions that work together with the hope that cardamom development can be positive and the existence of social interactions that enable hopes to be realized such as obligations and joint responsibility. Keywords: network, charamon, social capital, norms, trust